2012
DOI: 10.1002/jbm.a.34134
|View full text |Cite
|
Sign up to set email alerts
|

New ureteral scaffold constructed with composite poly(L‐lactic acid)–collagen and urothelial cells by new centrifugal seeding system

Abstract: A tissue-engineered ureteral scaffold was constructed with composited poly L-lactic acid (PLLA)-collagen endoluminal stent and uroepithelial cells (UECs) using a new seeding system. The electrospun PLLA-collagen nanofibrous mesh was seeded efficiently with human ureteral epithelial cells using a modified centrifugal seeding device. The cellular nanofibrous mesh was then wound around a spiral endoluminal stent to form a cellular composited PLLA-collagen ureteral scaffold. The cellular ureteral scaffold was subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 43 publications
(69 reference statements)
0
29
0
1
Order By: Relevance
“…This way the initial tissue contraction takes place in a more controlled environment, without the toxic influences of urine (Adamowicz et al , ). Recent studies have shown the successful application of these techniques by implanting the tissue in non‐functional locations (Fu et al , ; Shi et al , ; Xu et al , ), as well as using them for ureteral repair afterwards (Liao et al , ; Zhang et al , ). Pre‐implantation before functional implantation may therefore improve the outcome of the reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…This way the initial tissue contraction takes place in a more controlled environment, without the toxic influences of urine (Adamowicz et al , ). Recent studies have shown the successful application of these techniques by implanting the tissue in non‐functional locations (Fu et al , ; Shi et al , ; Xu et al , ), as well as using them for ureteral repair afterwards (Liao et al , ; Zhang et al , ). Pre‐implantation before functional implantation may therefore improve the outcome of the reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Such engineered tissue can be useful in the future for ureteral reconstruction. There are some reports of autologous urothelial cell transplantation (23,24) and ureteral reconstruction using autologous tubular grafts in animal models with good results (25,26). Analysis of the ureteral structure in anencephalic fetuses could be important in future studies of tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…9 Briefly, four cell-seeded SIS prepared using different seeding methods were incubated for 24 h. Four randomly chosen compound SIS from each group were cut into squares with a surface area of 0.2 cm 2 . The SIS squares were washed two times with serumfree media and transferred to a 96-well plate.…”
Section: Assessment Of Cell Viabilitymentioning
confidence: 99%
“…Several methods are currently used to facilitate cell seeding, such as the sandwich co-culture method, the layered co-culture method, the agitation seeding method, and the centrifugation seeding method. [7][8][9] Few studies have optimized cell-seeding and subsequent culture conditions that correlate with the physiological and mechanical reinforcement of biomaterials. The experimental use of commercial four-layer small intestinal submucosa (SIS) (Cook Deutschland, Germany) for the reconstruction of different segments of the urinary tract has shown promising results.…”
Section: Introductionmentioning
confidence: 99%